PENGARUH IMPLEMENTASI E-PROCUREMENT DAN AKUNTABILITAS TERHADAP EFISIENSI PENGADAAN BARANG DAN JASA PADA DINAS PERHUBUNGAN KABUPATEN PROBOLINGGO - Agung Yatiningrum; Yayuk Indah Wahyuning Tyas (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This research was conducted at the Department of Transportation of Probolinggo Regency with the aim that the research to be achieved can determine the effect simultaneously and partially between E-Procurement and Accountability for Procurement Efficiency and to determine the variables between E-Procurement and Accountability which have a dominant effect for the Efficiency of the Goods Procurement and Services at the Probolinggo Regency Transportation Service. The type of this research is descriptive quantitative research type with the variables used include e-procurement, accountability, and procurement efficiency. The method of data analysis from this research is descriptive quantitative method using statistics in the form of multiple regression analysis, multiple correlation analysis, and analysis of determination. The results showed that E-procurement and Accountability for Procurement Efficiency at the Department of Transportation of Probolinggo Regency aimed at multiple regression equations, namely Y = 5,386 + 0.635X1 + 0.079X2 and the simultaneous hypothesis test results showed that the value of Fcount = 6.827 was greater than the value of Ftable = 3. , 29 (Fcount> Ftable) proves that there is a simultaneous significant influence between E-Procurement and Accountability on Procurement Efficiency at the Department of Transportation, Probolinggo Regency. The results of the partial hypothesis test show that the value of tcount X1 = 3.558 and the value of tcount X2 is 2.717 greater than the value of ttable = 1.694 (tcount  ttbel) which proves that there is a significant influence between E-procurement and Accountability on Procurement Efficiency in the Transportation Agency, Probolinggo Regency. The dominant E- Procurement variable has an effect on Procurement Efficiency at the Transportation Agency of Probolinggo Regency. Procurement Efficiency of 61.8% is influenced by E-Procurement and Accountability, while the remaining 38.2%, the amount of Procurement Efficiency is influenced by other variables that are not examined.